What Makes Police Officers Act? Police Response to Instances of Intimate Partner Violence - Peirone, Amy (Journal of interpersonal violence, 2021)
Using data from the 2009 General Social Survey (GSS Cycle 23: Victimization main file), this study assessed the relationship between individual and neighborhood-level factors and police response to spousal violence in Canada. A total of 890 participants in the GSS reported experiences of spousal violence within the previous 5 years, with approximately 22% of these victims reporting direct contact with the police because of the violence. Among this subsample of victims who had police contact, we evaluated the extent to which individual-level factors (sociodemographic and violence characteristics) and neighborhood-level factors (perceptions of social disorder and the presence of police facilities in one’s community) were related to distinct types of police response to reported spousal violence. Regression analyses suggest variations in police response based on sociodemographic, violence, and neighborhood characteristics; however, overall satisfaction with police actions taken were not found to be significantly different among victims based on these characteristics. Implications are relevant for policing practice as results suggest that different victims may have different safety needs and abilities to communicate these needs to the police.